Nutritional and metabolic changes in patients with aids in antiretroviral therapy - Silva, Maria Clara A.; Burgos, Maria Goretti Pessoa de Araújo; Silva, Rafaella A. (Brazilian Journal of Sexually Transmitted Diseases, 2010)
Introduction: nutritional changes and its complications can become HIV-positive individuals more suscetible to opportunistic infections and reduce the effectiveness of medicines. Objective: assess the nutritional and metabolic changes in patients with AIDS, in antiretroviral theraphy treated at outpatient treatment at a hospital in Northeast Brazil. Methods: we studied 31 patients across, patient clinic, using the anthropometric and biochemical parameters. Results: Patients were classified as normal according to BMI, but showed reduction of adipose reserves in the upper limbs, reflecting lipodystrophy associated with mixed dyslipidemia, as probable consequence of HAART. Anemia was found in both sexes. The time of diagnosis did not correlate with nutritional status. Conclusion: nutritional and metabolic changes in aids patients can be minimized through proper drug therapy and diet therapy.